Self assembled CdLa2S4 hexagon flowers, nanoprisms and nanowires: novel photocatalysts for solar hydrogen production - Kale, Bharat B.; Baeg, Jin-Ook; Kong, Ki-jeong; Moon, Sang-Jin; Nikam, Latesh K.; Patil, Kashinath R. (Journal of Materials Chemistry, 2011)
We report here a new ternary chalcogenide material, cadmium lanthanum sulfide (CdLa2S4) produced using a facile hydrothermal method at 433 K. The effect of the solvent on the morphology of the CdLa2S4 was demonstrated for the first time. The prima facie observations revealed the formation of highly crystalline hexagonal structures in the form of flowers in aqueous medium. The flowers comprise hexagonal columns similar to 300 nm in diameter and 1-1.2 mu m in length. All the hexagonal structures have a sharp tip with a cavity of 10 nm and are almost equal in size. The nanoprisms have an average base size of 35 nm with 35 nm edges, and the nanowires have a diameter of 10-15 nm; both were obtained in methanol. Crystal and electronic structure calculations were performed using the Vienna ab initio simulation package (VASP) based on density functional theory (DFT). Considering the band gap of pristine CdLa2S4 in the visible region (2.3 eV), we have demonstrated CdLa2S4 as a photocatalyst for the production of H-2 under solar light. Nanostructured CdLa2S4 prisms gave the maximum hydrogen production, i.e. 2552 mu mol h(-1). Being a stable ternary nanostructured metal sulfide (with nanohexagons, nanoprisms, nanowires), CdLa2S4 may have other potential prospective applications in solar cells and optoelectronic devices.

Spin transport and magnetic correlation parameters for graphene-like nanocarbon sheets doped with nitrogen - Alegaonkar, Ashwini P.; Kumar, Arvind; Patil, Sagar H.; Patil, Kashinath R.; Pardeshi, Satish K.; Alegaonkar, Prashant S. (Journal of Physical Chemistry C, 2013)
Globally, graphene magnetism has captivated the attention of researchers in recent years. To obtain magnetic ordering, irregularities in the carbon network, like defects, adatoms, etc., are essential. Herein, we report on spin transport and magnetic correlations in graphene-like nanocarbon sheets (GNCs) that were doped with nitrogen by use of tetrakis(dimethylamino)ethylene (TDAE). The spin transport measurements, performed by electron spin resonance technique, showed that both spin-spin and spin-lattice relaxation times are increased by nitrogen doping. The magnetic correlations, measured on a vibrating sample magnetometer, showed that ordering parameters are reduced for nitrogen-loaded GNCs. Chemical analysis, carried out via electron spectroscopy, revealed that nitrogen atoms exchange couples electron-to-hole with the carbon network Analysis of I-V measurements showed that higher-order resistance is appreciably decreased for nitrogen-doped GNCs. The observed decrease is due to an increase in nonbonding states baying small local density. After doping, states in this region may be localized pi spin populated around the doped region. By and large, the approximately 20% magnetization that exists in GNCs is found to be reduced to 5% by introduction of nitrogen.

Studies on morphology of polyaniline films formed at liquid-liquid and solid-liquid interfaces at 25 and 5 A degrees C, respectively, and effect of doping - Waghmode, Babasaheb J.; Patil, Sagar H.; Jahagirdar, Mandar M.; Patil, Virendra S.; Waichal, Rupali P.; Malkhede, Dipalee D.; Sathaye, Shivaram D.; Patil, Kashinath R. (Colloid and Polymer Science, 2014)
It is well accepted that the morphology of the nanomaterials has great effect on the properties and hence their applications. Therefore, morphology of materials has become a focus of research in the scientific world. The present study shows that interfacial polymerization and subsequent self-assembly provides a control over the morphology, nanorod/nanosheet, of polyaniline (PANI) films synthesized by liquid-liquid interface reaction technique and solid-liquid interface reaction technique. The synthesized PANI films and its particulate structure are characterized by using various spectroscopic techniques such as UV-visible, ATR-IR, Raman and XPS. The study confirmed the formation, the structure, the size and shape of particles and morphology of PANI by using analytical techniques namely, SAED, SEM and TEM. An important observation is that doping with HCl significantly improves the nanorod formation at the interface. The doped PANI electrode exhibits a higher area with rectangular shape in CV cycle and better cycle stability when compared with the performance of undoped PANI films. We believe that the results of these studies can give valuable leads to manoeuvre formation of PANI films with desired morphology for various applications.
Keywords: interfacial polymerization; Liquid-liquid interface; Nanorods; nanosheets; polyaniline; Self-assembly; Solid-liquid interface; Thin films

Shape-selective oriented cerium oxide nanocrystals permit assessment of the effect of the exposed facets on catalytic activity and oxygen storage capacity - Sreeremya, Thadathil S.; Krishnan, Asha; Remani, Kottayilpadi C.; Patil, Kashinath R.; Brougham, Dermot F.; Ghosh, Swapankumar (ACS Applied Materials & Interfaces, 2015)
The catalytic performance of a range of nanocrystalline CeO2 samples, prepared to have different morphologies, was measured using two accepted indicators; oxygen storage and diesel soot combustion. The same powders were characterized hi detail by HR-TEM, XRD, XPS, and Raman methods. The study demonstrates that activity is determined by the relative fraction of the active crystallographic planes, not by the specific surface area of the powders. The physical study is a step toward quantitative evaluation of the relative contribution to activity of the different facets. The synthetic protocol permits fabrication of CeO2 nanostructures with preferentially grown active planes, and therefore has potential in developing catalytic applications and in nanocompositing.
Keywords: ceria; chemical activities; crystal facets; nanocrystals; texture coefficient

Synthesis and characterization of FeTiO3 ceramics - Gambhire, Anil B.; Lande, Machhindra K.; Rathod, Sandip B.; Arbad, Balasaheb R.; Vidhate, Kaluram N.; Gholap, Ramakrishna S.; Patil, Kashinath R. (Arabian Journal of Chemistry, 2016)
Nanocrystalline FeTiO3 ceramics powders were prepared by the sol-gel process combined with a surfactant-assisted template method. The resulting powders were calcined at different temperatures ranging from 150 degrees C to 600 degrees C for 2 h in an air. The results revealed that a pure hexagonal phase of FeTiO3 could be obtained at low temperature, 600 degrees C. The phase evolution of FeTiO3 was investigated by X-ray diffraction patterns (XRD), Fourier-transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). Particle size and morphology was studied by transmission electron microscopy (TEM). (C) 2011 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Electron microscopy; hexagonal phase; Nanoparticles; sol-gel process; Ti-O bond

Synthesis and study of calixarene-doped polypyrrole-TiO2/ZnO composites: antimicrobial activity and electrochemical sensors - Waghmode, Babasaheb J.; Husain, Zahid; Joshi, Meenal; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (Journal of Polymer Research, 2016)
The present communication describes the synthesis of an electroactive nanocomposite of calixarene- doped polypyrrole ( PPY) containing an oxide of Ti/ Zn. The additive TiO2/ ZnO serves as an oxidizing agent for the polymerization, thus avoiding the use of hazardous organic solvents while calixarene doping stabilizes the polymer. The materials synthesized herein were characterized by UV- visible spectroscopy, FT- IR spectroscopy, scanning electron microscopy ( SEM), transmission electron microscopy ( TEM), energy- dispersive X- ray spectroscopy ( EDX), X- ray photoelectron spectroscopy ( XPS), and cyclic voltammetry ( CV) of synthesized nanocomposites. It was revealed that the resulting calixarene- doped polypyrrole- TiO2/ ZnO nanocomposite has ( 1) long- time stability, ( 2) significant electrochemical activity for sensing formaldehyde, and ( 3) good antimicrobial activity.